What Explains Changes In Accounting Divisional Performance Under Liquidity Shortage Conditions? Evidence from the Greek Banking - Eleftherios Aggelopoulos (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This is the first study which tests empirically to which extent the quality and the spread of consumer and small business loans are responsible for the increases or decreases in branch accounting performance, measured by the Residual Income (RI) performance indicator, over time. Moreover, given extreme liquidity shortage conditions the paper investigates to which extent the above factors are responsible for changes in RI. Unique accounting information derived from the Management Information System (MIS) of a Greek systemic commercial bank is utilized. The study finds that lending spreads for both types of loans are positively and statistically significant related to RI. The crisis increases the positive value effect of consumer lending spreads while reduces the value premium of small business lending spreads. The latter indicates that the upward repricing of small business credit lines during crisis years seems to destroy value due to the side effects that the repricing loan policy activates (i.e. reduces the repayment ability of borrowers). Moreover, the enormous increase of loan loss impairments during crisis exercises an extra negative impact on RI thus further accelerating shareholder value destruction, for both loan portfolios. The study provides useful information about the thorough understanding of the quality of banking performance at the retail level in bank-driven crisis economies.
Keywords: M41; G21; 650; Divisional performance; lending operations; retail branches; spread and credit risk; crisis